Evaluación de la disminución en la carga contaminante de los colorantes asociados a la tinción de Gram mediante carbón activado encapsulado en alginato de sodio (2019)
The present work has as main objective the decrease in the pollutant load of the dyes associated with the staining of large (Violet crystal, fuchsin) and methylene blue of wastewater from the microbiology laboratory of the Pontificia Universidad Javeriana through the approach of an activated carbon adsorption system obtained from tire pyrolysis and encapsulated in sodium alginate. Two assemblies of adsorption systems were raised, both performed in batch operation mode. The first involves the use of a beaker and the second with the use of glass instruments (Columns) in order to evaluate an approach to a column adsorption system.